2014
DOI: 10.1001/jamainternmed.2014.1608
|View full text |Cite
|
Sign up to set email alerts
|

Preventing 30-Day Hospital Readmissions

Abstract: IMPORTANCE Reducing early (<30 days) hospital readmissions is a policy priority aimed at improving health care quality. The cumulative complexity model conceptualizes patient context. It predicts that highly supportive discharge interventions will enhance patient capacity to enact burdensome self-care and avoid readmissions.OBJECTIVE To synthesize the evidence of the efficacy of interventions to reduce early hospital readmissions and identify intervention features-including their impact on treatment burden an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
316
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 632 publications
(326 citation statements)
references
References 64 publications
7
316
2
1
Order By: Relevance
“…The timing of 30‐day readmissions highlights the importance of both early outpatient care and longitudinal surveillance strategies within 30 to 90 days following hospitalization 18. Measures focusing on supportive discharge interventions have been shown to enhance patient capacity for self‐care and have helped to avoid readmissions 19. Comprehensive programs that focus on both inpatient and outpatient interventions and utilize tools that facilitate cross‐site communication can lead to a decrease in early readmissions 20, 21.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of 30‐day readmissions highlights the importance of both early outpatient care and longitudinal surveillance strategies within 30 to 90 days following hospitalization 18. Measures focusing on supportive discharge interventions have been shown to enhance patient capacity for self‐care and have helped to avoid readmissions 19. Comprehensive programs that focus on both inpatient and outpatient interventions and utilize tools that facilitate cross‐site communication can lead to a decrease in early readmissions 20, 21.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,23,34 However, given the complexity of caring for patients with SAH, the role of early follow-up (e.g., within 1 week of discharge) with a primary care physician in preventing readmission may warrant further investigation in this unique population. Recent work has also emphasized the effectiveness of complex, multifaceted strategies in reducing readmission, 18 and a combination of multiple inpatient and outpatient strategies could also be impactful in preventing rehospitalization after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…6 With cumulative complexity in mind, a systematic review found that the most effective interventions for reducing 30-day readmissions in nonstroke populations were the ones that comprehensively increased patient capacity for self-care, had a higher number of intervention activities and interactions, and had ≥2 individuals involved in its delivery (relative risk, 0.63; 95% confidence interval, 0.43-0.91; P=0.02). 7 In stroke patients, a recent systematic review reported that less than half of transitional care models were successful at improving outcomes, and none actually reduced emergency department or hospital readmissions. 8 Because of the variability of stroke transitional care model interventions, Prvu Bettger et al 9 …”
mentioning
confidence: 99%